2016
DOI: 10.1007/s00259-016-3420-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RECIST, EORTC criteria and PERCIST for evaluation of early response to chemotherapy in patients with non-small-cell lung cancer

Abstract: EORTC criteria and PERCIST 1.0 are more sensitive and accurate than RECIST 1.1 for the detection of an early therapeutic response to chemotherapy in patients with NSCLC. Although EORTC criteria and PERCIST 1.0 showed similar results, PERCIST 1.0 is preferred because detailed and unambiguous definitions are given. We also found that response evaluations with PERCIST 1.0 using a single lesion and multiple lesions gave similar response classifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 28 publications
2
46
0
1
Order By: Relevance
“…Of the 19 patients having SD according to RECIST, 14 patients were reclassified as having PMR according to PERCIST, showing that metabolic changes exceeded the threshold criteria earlier than morphologic changes. A prospective study by Shang et al (26) comparing RECIST, PERCIST, and European Organisation for Research and Treatment of Cancer (EORTC) criteria for evaluation of early response (after 2 wk) to chemotherapy in NSCLC patients showed that both PERCIST and European Organisation for Research and Treatment of Cancer criteria were more accurate in predicting an early response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 patients having SD according to RECIST, 14 patients were reclassified as having PMR according to PERCIST, showing that metabolic changes exceeded the threshold criteria earlier than morphologic changes. A prospective study by Shang et al (26) comparing RECIST, PERCIST, and European Organisation for Research and Treatment of Cancer (EORTC) criteria for evaluation of early response (after 2 wk) to chemotherapy in NSCLC patients showed that both PERCIST and European Organisation for Research and Treatment of Cancer criteria were more accurate in predicting an early response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reader should note that only two short extra steps are needed to perform PERCIST. First, the reader is required to measure the hepatic 18 F-FDG activity. In order to perform PERCIST, the reader needs to see if the target tumor lesion shows sufficiently high glucose uptake for reliable assessment using 18 F-FDG PET/ CT. PERCIST has a minimum threshold for measurability, defined as 1.5 × (mean value of normal liver) + 2 × (standard deviation of liver) or greater at baseline.…”
Section: Performing Percistmentioning
confidence: 99%
“…In 20 patients with metastatic breast cancer, tumor response by PERCIST was a superior predictor of progressionfree survival (PFS) than response by RECIST 1.1 [17]. PERCIST showed difference in PFS between the patients with partial metabolic response and stable metabolic disease, while the PFS did not significantly differ between the partial remission and stable disease groups according to RECIST 1.1 after chemotherapy in 35 patients with non-small-cell lung cancer (NSCLC) [18]. There are additional studies that showed superior predictive value of PERCIST compared to RECIST 1.0 in esophageal cancer, NSCLC, and Ewing sarcoma [19][20][21].…”
Section: Comparison Of Percist With Recistmentioning
confidence: 99%
See 2 more Smart Citations